Economic Evaluation of Cardiovascular and Diabetes Prevention in Primary Care: A Systematic Review - Aulia Abdillah Ramadhan; Kurnia Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Cardiovascular disease (CVD) and diabetes are major contributors to global morbidity and mortality. Prevention programs implemented in primary care settings—such as the WHO HEARTS initiative and lifestyle-based diabetes interventions—have gained attention for their potential clinical and economic impact. To systematically review economic evaluations of cardiovascular and diabetes prevention programs delivered in primary health care, focusing on cost-related outcomes and economic value. A systematic search of PubMed, Scopus, and ScienceDirect identified studies published from 2016 to 2025 that reported economic outcomes of CVD or diabetes prevention interventions in primary or community healthcare. Data extracted included intervention types, cost estimates, quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs), and cost drivers. Study quality was assessed using the CHEERS checklist. Twelve studies met inclusion criteria. Most demonstrated favorable cost-effectiveness, with ICERs ranging from USD 105 to USD 14,011 per QALY. Integrated programs addressing both hypertension and diabetes were generally more cost-efficient. Medications, diagnostics, and human resources were the primary cost drivers. Economic evaluations indicate that preventive interventions for CVD and diabetes in primary care are cost-effective across various health system contexts. Scalable models like HEARTS, when adapted locally, can support both health impact and efficient resource use